Chapter 2.4 Research Management as Labyrinthine – How and Why People Become and Remain Research Managers and Administrators Around the World - Susi Poli; Simon Kerridge; Patrice Ajai-Ajagbe; Deborah Zornes (Emerald Publishing Limited, 2023)
This chapter explores the results of an international survey (RAAAP-2) to provide global insight into research management and administration (RMA) as a relatively new field of investigation within the area of higher education management (HEM). Building on that extensive survey, the purpose of this chapter is to investigate qualitatively how and why people become and remain research managers and administrators, focussing primarily on their skills, roles, and career paths. Findings from the analysis confirm that a career in RMA is rarely an intentional choice and can be described as labyrinthine , which could be even compared and contrasted with a concertine academic career described by Whitchurch et al. (2021). While conclusions confirm the gender implications of the profession, which is overall highly `female'; further conclusion sheds light on RMAs across regions and suggests how this varied ecosystem could even undermine the recognition of RMA as a profession.
10.1108/978-1-80382-701-820231013; 10.1108/978-1-80382-701-820231013; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262